Self - treatment with drugs during gestation - Ziaie, T; Ozgoli, G; Yaghmaei, F; Akbarzade, A (Advances in Nursing & Midwifery, 2009)
Background Pregnancy due to its nature is associated with some problems, which may increase the need for drugs. Drug self-treatment can cause severe complications and lack of information of mothers concerning the indications of drugs may have detrimental effects on family as well as society. Purpose This descriptive study was conducted to identify knowledge, attitude and practice of pregnant women regarding self-treatment with drugs in healthcare settings affiliated to Shaheed Beheshti Medical University in 2006. Methods 180 pregnant women referring to healthcare centers were selected in 2 steps by cluster sampling method. The stage of their gestational period was not important. An information form was used for data collection. Results Findings showed that 98.3% of women knew the forbiddance of chemical drugs during pregnancy without prescription. 70.6% agreed chemical drug prescription by a professional. Of 180 women, 100 (55.5%) took chemical drugs during their pregnancy and 97.8% used the drugs by prescription. 11.1% took herbs by prescription while 84.2% used them without prescription and by recommendation of their acquaintances or their own views. 4.7% took herbs by suggestion of herbalists. Conclusion It can be concluded that despite good knowledge of women about indications of chemical drugs, their information regarding herbs is not satisfactory. Therefore, developing appropriate educational plans in media, healthcare settings and prenatal clinics to improve their knowledge seems necessary. Keywords: Knowledge, Attitude, Practice, Self-treatment, Pregnant women.